Spatial–temporal pattern and drivers associated with measles resurgence from 2018 to 2023: a global perspective from 192 countries - Jingzhi Li; Ying Shen; Xiang Xu; Xiaoli Wang; Zhuowei Luo (BMJ Public Health)
Introduction The resurgence of measles, a highly contagious infectious disease, has become a serious global public health issue. In this study, we aimed to explore global spatial–temporal measles trends and the underlying causes to help formulate effective intervention strategies.Methods We analysed measles incidence data from 192 countries, integrating measles vaccination coverage from WHO/UNICEF Estimates of National Immunization Coverage, armed conflict data from the Uppsala Conflict Data Program and gross domestic product (GDP) per capita and population data from the World Bank’s World Development Indicators. Hot spot analysis, mean centre and standard deviational ellipse models were used to examine the geographic and temporal shifts in measles outbreaks. A negative binomial mixed‐effects model was then constructed to determine the influence of population size, GDP per capita, measles vaccine coverage and armed conflict on measles incidence.Results Our findings showed a pronounced southward shift in measles outbreaks from Southeast Asia to sub-Saharan Africa between 2018 and 2019, followed by a northward progression towards Europe from 2019 to 2023. The negative binomial model indicated that armed conflict significantly increased measles incidence (estimate=1.131, p<0.05) and that higher second dose of measles vaccine (MCV2) coverage reduced incidence (estimate=–0.052, p<0.05). Additionally, regions with lower GDP per capita experienced elevated measles burdens, reflecting resource constraints and diminished vaccination infrastructure.Conclusions Ensuring robust two-dose vaccination coverage, particularly for MCV2, remains critical for reducing measles incidence worldwide. These results underscore the importance of tailored interventions, especially in conflict‐affected and lower‐income regions. Enhanced spatiotemporal surveillance and targeted public health initiatives can help address both the direct impact of armed conflict on health systems and the broader socioeconomic drivers that facilitate measles outbreaks.